2021
DOI: 10.1007/s11136-021-02872-8
|View full text |Cite
|
Sign up to set email alerts
|

An item analysis according to the Rasch model of the German 12-item WHO Disability Assessment Schedule (WHODAS 2.0)

Abstract: Purpose The World Health Organization Disability Assessent Schedule 2.0 (WHODAS 2.0) assesses disability in individuals irrespective of their health condition. Previous studies validated the usefulness of the WHODAS 2.0 using classical test theory. This study is the first investigating the psychometric properties of the 12-items WHODAS 2.0 in patients with cancer using item analysis according to the Rasch model. Methods In total, 350 cancer patients partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…After adjustments to the modification indices, the model tested by the confirmatory factor analysis identified a single factor in the WHODAS 2.0 structure. Although different populations and health conditions are assessed, the generic version of the WHODAS 2.0 also had a single-factor structure [ 9 , 14 , 15 ]. In Brazilians with Chagas disease, WHODAS 2.0 showed 3 factors with adequate global internal consistency (Alpha = 0.87) [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After adjustments to the modification indices, the model tested by the confirmatory factor analysis identified a single factor in the WHODAS 2.0 structure. Although different populations and health conditions are assessed, the generic version of the WHODAS 2.0 also had a single-factor structure [ 9 , 14 , 15 ]. In Brazilians with Chagas disease, WHODAS 2.0 showed 3 factors with adequate global internal consistency (Alpha = 0.87) [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have reported different factor structures (e.g., one-factor [ 14 , 15 ], 3-factor [ 16 ], 4-factor [ 17 ], and 6-factor [ 18 , 19 ]) for the 12-item WHODAS 2.0 in varied populations and health conditions that include men and women [ 14 – 19 ]. Thus, it was necessary to assess the structural validity of this WHODAS 2.0 version in a sample of women with dysmenorrhea by exploratory factor analysis and confirmatory factor analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Over the past two decades, IRT and Rasch models have been applied to disability measurements (usually as complements to classical methods such as correlation and factor analysis) in numerous studies that aimed to: 1) investigate the psychometric properties of the newly developed WHO Disability Assessment Schedule (WHODAS) [ 22 , 23 ] and the Model Disability Survey (MDS) instruments of the WHO and World Bank [ 24 26 ]; 2) investigate stability over time and settings of measures based on ADL, IADL, or both [ 27 31 ]; and 3) develop new measures of functioning using existing ADL and IADL subsets [ 32 35 ]. Though not the specific aims of these studies, various problems associated with ADL and IADL items have been identified concerning the response categories [ 27 29 , 32 , 35 ], strength of unidimensional continuum and redundancy of items [ 31 33 ], and DIF with regard to gender [ 30 , 34 , 35 ] and age [ 34 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…Its application is well suited whenever new patient-reported outcome measures (PROMs) shall be developed, for example, 16,17 or whenever existing PROMs shall be reviewed and where necessary be revised. [18][19][20][21][22] It possesses desirable mathematical properties and allows for a unified approach to simultaneously investigate several measurement issues 23,24 as unidimensionality, local independence, differential item functioning (DIF) and targeting.…”
Section: Introductionmentioning
confidence: 99%
“…This is supported when looking more closely to the items showing the DIF with regard to receiving an injectable antidiabetic drug. In fact, the DIF is related to the items from the "Follow-up/Coordination"-subdimension (Items[16][17][18][19][20] which reflect how far the attending doctor coordinates and supervises the treatments of other health services. This could indicate a slight difference in treatment of patients receiving an injectable antidiabetic drug-with the difference being especially pronounced with regard to the 'Follow-up/Coordination'-aspect.Regarding the dimensionality of the PACIC-20, we found that the PACIC-20 can indeed be regarded as a unidimensional scale including all 20 items if the huge amount of response dependency across items is accounted for.…”
mentioning
confidence: 99%